1997
DOI: 10.1681/asn.v8121877
|View full text |Cite
|
Sign up to set email alerts
|

Verocytotoxin inhibits mitogenesis and protein synthesis in purified human glomerular mesangial cells without affecting cell viability

Abstract: Acute renal failure is one of the hallmarks of the hemolytic uremic syndrome (HUS). Infection with a verocytotoxin (VT)- or Shiga-like toxin (SLT)-producing Escherichia coli has been strongly implicated in the etiology of the epidemic form of HUS. The functional receptor for these closely related toxins appears to be a glycosphingolipid, globotriaosylceramide (Gb3). Endothelial damage in the glomeruli and arterioles of the kidney induced by VT is believed to play a crucial role in the pathogenesis of HUS. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The pathogenetic mechanisms leading to acute renal failure during EHEC-associated HUS are associated with prothrombotic vascular injury, as outlined above, triggering the formation of occluding microthrombi in glomeruli, as well as acute toxin-induced tubular injury [59,113]. The toxin itself reaches the kidney [69][70][71] affecting glomerular (endothelial cells, podocytes and mesangium) and tubular cells [59,[114][115][116]. In addition, there is activation and influx of neutrophils, corresponding to the severity of renal failure [117,118], and of platelets within microthrombi [109].…”
Section: Renal Failurementioning
confidence: 99%
“…The pathogenetic mechanisms leading to acute renal failure during EHEC-associated HUS are associated with prothrombotic vascular injury, as outlined above, triggering the formation of occluding microthrombi in glomeruli, as well as acute toxin-induced tubular injury [59,113]. The toxin itself reaches the kidney [69][70][71] affecting glomerular (endothelial cells, podocytes and mesangium) and tubular cells [59,[114][115][116]. In addition, there is activation and influx of neutrophils, corresponding to the severity of renal failure [117,118], and of platelets within microthrombi [109].…”
Section: Renal Failurementioning
confidence: 99%
“…It has been argued consistently that widespread Stx-mediated endothelial injury of pulmonary capillaries contributes to the development of lung involvement in HUS [6]. Recent studies, however, have shown that Stx directly affects several different cell types, including B lymphocytes [22], macrophages/monocytes [23,24], renal tubular epithelial cells [25][26][27][28], and mesangial cells [29,30]. These reports indicate that endothelial cell damage may not be the sole cause of HUS and that further investigation is required to understand this disease.…”
mentioning
confidence: 99%